The Relationship Between Stress and Temporomandibular Disorder in Students of the Faculty of Dentistry, Baiturrahmah University Class of 2020 - Rahmad, Yulia; Edrizal, Edrizal; Berhana, Angela Toberianida Oceania (Odonto : Dental Journal, 2024)
Background: Stress is a physiological response in the form of worry or mental tension in the face of a difficult situation. With high study demands, dental students often experience stress. Uncontrolled stress can have adverse effects on physical and bodily functions, one of which can increase the risk of temporomandibular disorder (TMD). Stress can trigger muscle hyperactivity which will cause fatigue in the temporomandibular joint.Methods: This research is an analytic observational study with a cross-sectional design. Respondents of this study were 95 students of the Faculty of Dentistry, Baiturrahmah University Class of 2020. Stress assessment was measured by the Student-Life Stress Inventory (SSI) questionnaire and temporomandibular disorder assessment was measured by the Helkimo Index (Anamnestic Index and Dysfunction Index). Results: The level of stress experienced by 69 people (72.6%) mild stress and 26 people (27.4%) moderate stress. Anamnestic index results were 47 people (49.5%) experiencing mild symptoms, 23 people (24.2%) experiencing severe symptoms and 25 people (26.3%) without symptoms. The results of the dysfunction index as many as 48 people (50.5%) experienced mild dysfunction, 40 people (42.1%) experienced moderate dysfunction and 2 people (2.1%) experienced severe dysfunction. The results of the chi-square test showed p=0.000 (p<0.05) there was a relationship between stress variables and temporomandibular disorder variables. Conclusion: There is a relationship between stress and temporomandibular disorder in Baiturrahmah University Faculty of Dentistry students class of 2020.